2023
DOI: 10.3389/ijph.2023.1605359
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Primary Care and Public Health in Medical Students’ Training Based on Social Accountability and Community-Engaged Medical Education

Abstract: Objectives: Primary care and public health comprise the bedrock of health systems, but their divergence has produced two groups of practitioners either focused on individual health or population health. We explored how primary care and public health were integrated in medical students’ training in Zamboanga Peninsula, Philippines.Methods: Our qualitative study reviewed community health plans in two municipalities and thematically analyzed the perspectives of medical students, faculty, alumni, and community sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It is also important to emphasise the need to strengthen the skills of local health officers to effectively carry out their responsibilities within an integrated healthcare setup. Providing capacity-building support for current officers while preparing future practitioners for this role holds great importance in sustaining the reform 26 27…”
Section: Lessons Learntmentioning
confidence: 99%
“…It is also important to emphasise the need to strengthen the skills of local health officers to effectively carry out their responsibilities within an integrated healthcare setup. Providing capacity-building support for current officers while preparing future practitioners for this role holds great importance in sustaining the reform 26 27…”
Section: Lessons Learntmentioning
confidence: 99%
“…In global health training, concerns have been raised about the potential harm of short-term student visits from universities in the North to communities in the South, especially when students lack the skills yet are allowed to deliver healthcare to local populations, or when students are insensitive to local culture and beliefs 24. Some have suggested that training institutions could be held to account for their global health programmes when they are evaluated based on the extent to which they enable community participation in their student immersion programmes, or include the work of Global South scholars in their curriculum 25 26. Reflexivity also has a role in fostering accountability through the critical examination of individual positionalities and the colonial legacies that shape how stakeholders relate in the global health space 27.…”
Section: Introductionmentioning
confidence: 99%
“…With time, public health is also trying to integrate new technologies, especially in education and promotion ( 3 ). Primary care and public health comprise the backbone of health systems, but their divergence has produced two groups of practitioners, either focused on individual health or population/public health ( 4 ). Public health education is a precursor to public health practice and essential to one's foundational knowledge and skillset.…”
Section: Introductionmentioning
confidence: 99%